Eksplorasi Kesulitan Siswa dalam Menyelesaikan Soal Higher Order Thingking Skills (HOTS) dengan Menggunakan Metode Polya pada Materi Perbandingan Trigonometri - Saiful Saiful; Diyah Ayu Rizki Pradita; Faridatun Guvroniah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study aims to determine the difficulties of students in solving Higher Order Thingking Skills (HOTS) problems by using the Polya method in Trigonometric comparison materials. This research is a descriptive qualitative research. The subjects of the study were 36 students in class X.1 of SMA Negeri 2 Situbondo. Data collection techniques use test questions, interviews and documentation. The test in the form of Higher Order Thingking Skills (HOTS) questions is carried out to measure students' abilities. Interviews were conducted on 6 students based on the category of ability level of test results. Data analysis was carried out using data induction and reduction theory. The test results showed that those who scored in the high-level category were 10 students (28%), the moderate-level category was 14 students (39%) and the low-level category was 12 students (33%). The conclusion of this study states that the difficulty of students in solving Higher Order Thinking Skills (HOTS) questions using the polya method, namely subjects with high-level categories, experience difficulties at the re-examination stage. Subjects with a moderate level category, experienced difficulties at the stage of implementing the plan and re-examining. Subjects with low-level categories experienced difficulties at all stages of polya, namely at the stage of understanding the problem, making a plan, implementing the plan and re-examining.